Greenland, Kjerulf Fjord and Hisinger Gletscher - Boyd, Louise Arner, 1887-1972 (1931)
August 1, 1931. Kjerulfs [Kjerulf] Fjord. Extreme inner end. In background; range of mountains forming eastern side of Hisinger Glacier [Hisinger Gletscher], seen south of L.A.B.'s Scoop Mt. [Mountain] At base of mountain is glacier which proved to be Hisinger Glacier [Hisinger Gletscher]. In background on right; L.A.B.'s Curry-comb Peak forming western side of Left Valley. Stream flows in northerly direction down Left Valley. In foreground: mouths of streams of Right and Left Valleys. Photo taken looking S.S.E. from floor of Main Valley at S.W. end, where it joins Right Valley.